FUTURE ORIENTATION: THE ROLE OF EXTRACURRICULAR ECONOMICS IN SHAPING STUDENTS' VISION - Istiqomah, Aulia; Sugiono, Sugiono; Forijati, Forijati (Nusantara Economics and Entrepreneurships Journals, 2024)
Future orientation in adolescents allows them to think about the circumstances they will experience in the future, for example about life welfare. This article analyzes the role of caring extracurricular-based economic education in shaping the future orientation of SMKN 2 Blitar students. The qualitative approach used in this research aims to understand certain phenomena or problems in depth through descriptive and contextual data analysis. This topic involves complex aspects in the relationship between extracurricular-based economic education and students' future orientation. This program helps students detail career interests, develop entrepreneurial skills, plan for the future, and change their view of success. Caring extracurricular-based economic education has proven that formal education can be enriched with practical experience, which supports students in achieving their potential in career planning and skills development. As a result, this program helps students achieve a brighter and more successful future in various fields.